Composite self-gelling powder as well as preparation method and application thereof
By preparing a composite self-gel powder, using the combination of specific chemical substances and nanomaterials, the problem of insufficient healing of existing dressings on infectious wounds is solved, effective inhibition of bacteria and inflammation and promotion of wound healing is achieved, and excellent photothermal conversion efficiency and antibacterial properties are achieved.
Patent Information
- Application Number
- CN202411799730.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing antibacterial and wound healing dressings are inconvenient to use, have limited effect on irregular wound healing, may cause further damage to the wound when changing the dressing, and it is difficult to effectively remove bacteria and inflammation causes, resulting in increased oxidative stress and slowing down healing.
A composite self-gel powder is provided, which is prepared by COF-Fe and CCOF-Fe obtained by specific reaction and treatment of 1,3,5-tris(4-aminophenyl)benzene, 2,5-dimethoxyterephthaldehyde, acetonitrile, acetic acid and iron phthalocyanine through specific reactions and treatment, combined with polyacrylic acid and polyacrylamide, and is prepared by freeze-drying and grinding, with antioxidant enzyme activity and photothermal properties, and can absorb tissue exudate quickly to form gels for bacterial infectious wound treatment.
This composite self-gel powder can effectively relieve wound oxidative stress, reduce the inflammatory environment, have excellent photothermal conversion efficiency, realize coordinated sterilization of photothermal treatment, promote rapid repair of infectious wounds, and has the advantages of convenient administration, strong adhesion, strong stability and good antibacterial properties.
Smart Images

Figure CN119587456A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite biomaterial preparation, and in particular to a composite self-gelling powder and a preparation method and application thereof. Background Art
[0002] Infected wounds pose a significant threat to human health. Compared with ordinary wounds, infected wounds are particularly difficult to heal due to persistent bacterial infection and severe inflammation. Existing antibacterial and wound healing dressings, such as antibacterial films, fibers, and hydrogels, usually require strict storage and use conditions, and therefore have defects such as inconvenience in use. They are also limited in promoting the healing of various irregular wounds and may even cause further damage to the wound when changing the dressing. In addition, many dressings are difficult to effectively remove bacteria and address the causes of inflammation, including reactive oxygen species (ROS) and tissue exudates, thus bringing new oxidative stress to the wound, exacerbating inflammation and slowing healing.
[0003] Biomimetic nanozyme technology can efficiently catalyze various biochemical reactions, and therefore plays a key role in biomedical applications. The superoxide dismutase (SOD)-catalase (CAT) cascade nanozyme converts superoxide anions (O2 - ) is converted into H2O2, and further decomposed into O2 to regulate ROS levels, showing great potential in alleviating wound hypoxia, reducing oxidative stress and improving wound healing. Most of the currently disclosed materials that simulate SOD and CAT activity contain a large amount of heavy metals or metal oxides, which pose a toxic risk. In contrast, carbon-based nanomaterials (such as materials with Fe-NC structure) containing trace or small amounts of non-heavy metals (such as Fe) are favored for their excellent biocompatibility and stable enzyme activity. However, these carbon-based nanomaterials still have many defects in the treatment of infected wounds, including: the preparation process requires the use of complex precursors; doping or acid washing after synthesis not only increases the difficulty of synthesis regulation, but also easily causes structural unevenness and insufficient activity and stability; enzyme activity is not high or enzyme activity is difficult to regulate, and has strong oxidase or peroxidase (POD) activity, which can affect the inhibitory activity of carbon-based nanomaterials against oxidative tension and inflammation; the existing technology lacks a preparation that can more conveniently apply materials with Fe-NC structure to wound sites, so that they can effectively kill bacteria and remove excess tissue exudates while resisting oxidation and inflammation. Summary of the invention
[0004] The purpose of the present invention is to address the defects in the above-mentioned prior art and provide a composite self-gelling powder having antioxidant enzyme activity and photothermal properties, capable of absorbing tissue exudate and quickly gelling, and used for the treatment of bacterial infected wounds, as well as a preparation method and application thereof.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a composite self-gelling powder, comprising the following steps:
[0007] (1) mixing 1,3,5-tri(4-aminophenyl)benzene, 2,5-dimethoxyterephthalaldehyde, acetonitrile, acetic acid and iron phthalocyanine and reacting for 5 to 36 hours to obtain a reaction solution;
[0008] (2) centrifuging the reaction solution, collecting the precipitate and drying it to obtain COF-Fe;
[0009] (3) calcining COF-Fe in an inert gas for 0.5 to 4 h to obtain CCOF-Fe;
[0010] (4) CCOF-Fe, polyacrylic acid, polyacrylamide and water are mixed, freeze-dried and ground for 5 to 20 minutes to obtain a composite self-gel powder.
[0011] Preferably, the mass ratio of the 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde mixed in step (1) is 6-15:5-10;
[0012] The mass ratio of the 1,3,5-tris(4-aminophenyl)benzene and iron phthalocyanine is 6-15:1.2-3;
[0013] The mass volume ratio of the mixture of 1,3,5-tri(4-aminophenyl)benzene and acetonitrile is 6-15 mg:15-25 mL;
[0014] The mass volume ratio of the mixture of 1,3,5-tris(4-aminophenyl)benzene and acetic acid is 6-15 mg:0.2-0.7 mL;
[0015] The reaction temperature in step (1) is 20-30°C.
[0016] Preferably, the centrifugal speed in step (2) is 800-1500 rpm, and the centrifugal time is 5-15 min;
[0017] The drying in step (2) is vacuum freeze drying, the vacuum freeze drying temperature is -60 to -20°C, and the vacuum freeze drying time is 6 to 24 hours;
[0018] The particle size of the COF-Fe in step (2) is 250 to 500 nm.
[0019] Preferably, the inert gas in step (3) is nitrogen or argon;
[0020] The calcination temperature in step (3) is 500-1000° C.
[0021] The particle size of the CCOF-Fe in step (3) is 200 to 450 nm.
[0022] Preferably, in step (4), the mass ratio of the CCOF-Fe, polyacrylic acid, polyacrylamide and water is 0.001-0.016:0.1-0.4:0.2-0.5:5-15.
[0023] Preferably, the molecular weight of the polyacrylic acid in step (4) is 120,000 to 300,000 Da, and the molecular weight of the polyacrylamide is 5,000,000 to 15,000,000 Da.
[0024] Preferably, the freeze-drying temperature in step (4) is -60 to -20°C, and the freeze-drying time is 6 to 24 hours.
[0025] The invention also provides composite self-gel powder prepared by the preparation method.
[0026] The invention also provides application of the composite self-gel powder in preparing antibacterial drugs.
[0027] The present invention also provides application of the composite self-gelling powder in preparing medicine for relieving and / or treating infectious wounds.
[0028] The present invention has the following technical effects and advantages:
[0029] The CCOF-Fe prepared by the present invention has antioxidant enzyme activity, which can convert superoxide anions in the wound site into hydrogen peroxide, and further into water and oxygen. It does not generate ROS during the wound healing period, so it can effectively relieve wound oxidative stress and reduce the wound inflammatory environment. At the same time, it has excellent photothermal conversion efficiency and can achieve photothermal therapy synergistic sterilization.
[0030] The composite self-gelling powder CCF@PP prepared by the present invention has the antioxidant activity and photothermal conversion activity of CCOF-Fe, can absorb tissue exudate to quickly form a gel and thus adhere to a moist wound, synergistically kill bacteria through the photothermal effect of the amino group of the CCF@PP gel and the nanozyme, and can utilize the antioxidant enzyme effect to reduce the inflammatory response of the wound, promote the healing of the infectious wound and the growth of fibroblasts, thereby synergistically achieving the rapid repair of the infectious wound, and has the advantages of convenient administration, strong adhesion, strong stability, good antibacterial performance, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The preparation process and treatment mechanism of composite self-gelling powder CCF@PP;
[0032] Figure 2 For each COF-Fex and CCOF-Fe x SEM images of COF-Fe x Figure b is the SEM image of each CCOF-Fe x SEM images and particle size statistics;
[0033] Figure 3 For each CCOF-Fe x The results of CAT and SOD activity determination, where Figure a is the results of oxygen production rate and oxygen production in each CAT enzyme reaction system; Figure b is the results of each CCOF-Fe x The results of SOD activity inhibition rate determination;
[0034] Figure 4 In the figure, Figure a is the SEM image of COF-Fe; Figure b is the SEM image of CCOF-Fe; Figure c is the TEM image of CCOF-Fe; Figure d is the STEM image of CCOF-Fe; Figure e is the HRTEM image of CCOF-Fe and the EDS-mapping characterization of the corresponding element mapping, including the EDS-mapping characterization of the C, O, N, and Fe element mapping; Figure f is the AC-TEM image of CCOF-Fe, in which circles and stars represent single atoms and clustered iron, respectively; Figure g is the XRD spectrum of COF-Fe and CCOF-Fe; Figure h is the Raman spectrum of COF-Fe and CCOF-Fe; Figure i is the N2 adsorption-desorption isotherms and pore size distribution curves of COF-Fe and CCOF-Fe; Figure j is the XPS spectrum characterization of C / N bond energy of COF-Fe and CCOF-Fe; Figure k is the XPS spectrum characterization of C / O bond energy of COF-Fe and CCOF-Fe;
[0035] Figure 5 In the figure, Figure a is the CAT activity determination results of COF-Fe and CCOF-Fe; Figure b is the SOD activity inhibition rate determination results of COF-Fe and CCOF-Fe; Figure c is the photothermal diagram of the near-infrared photothermal performance of COF-Fe and CCOF-Fe; Figure d is the CAT activity determination results of CCOF-Fe at different pH; Figure e is the SOD activity determination results of CCOF-Fe at different pH; Figure f is the photothermal temperature of CCOF-Fe under near-infrared radiation cycle; Figure g is the CAT kinetic curve of CCOF-Fe at different H2O2 concentrations; Figure h is the SOD kinetic curve at different CCOF-Fe concentrations; Figure i is the photothermal efficiency analysis of CCOF-Fe; Figure j is the ABTS free radical scavenging ability characterization of COF-Fe and CCOF-Fe; Figure k is the ESR spectrum characterization of superoxide anions in the presence of CCOF-Fe; Figure l is a schematic diagram of the cascade enzyme activity process of CCOF-Fe scavenging free radicals;
[0036] Figure 6 For each gel powder PP x Preparation process;
[0037] Figure 7 For each PP x Adhesion test results of gel;
[0038] Figure 8 For each composite self-gel powder CCF@PP x Preparation process;
[0039] Fig. 9 Figure a shows the composite self-gel powder CCF@PP x The gelation time of each composite self-gel powder CCF@PP x Figure c shows the stress-strain curves of each CCF@PP x The results of water absorption test of gel;
[0040] Fig.10 In the figure, Figure a shows the preparation process of the composite self-gelling powder CCF@PP and the SEM image of the composite self-gelling powder CCF@PP; Figure b shows the heart shape molded by the composite self-gelling powder CCF@PP and the self-gelling effect with stretchability and adaptability; Figure c shows the adhesion effect of the composite self-gelling powder CCF@PP on pig skin, heart and intestine respectively; Figure d shows the infrared spectra of PAA, PAM, self-gelling powder PP and composite self-gelling powder CCF@PP; Figure e shows the oscillation time scanning curve of the composite self-gelling powder CCF@PP; Figure f shows the strain scanning curve of the composite self-gelling powder CCF@PP; Figure g shows the CAT activity of the composite self-gelling powder CCF@PP at different pH values; Figure h shows the SOD activity of the composite self-gelling powder CCF@PP at different pH values and the photothermal imaging after near-infrared irradiation for different times; Figure i shows the characterization of the ABTS free radical scavenging ability of the composite self-gelling powder CCF@PP;
[0041] Fig.11Figure a shows the agar plate culture results of Staphylococcus aureus ATCC6538 under different treatments; Figures b and c show the survival rate of Staphylococcus aureus ATCC6538 under different concentrations of CCOF-Fe and PP gel treatments, where C1 is 0 μg / mL, C2 is 65 μg / mL, C3 is 125 μg / mL, C4 is 250 μg / mL, C5 is 500 μg / mL, and C6 is 1000 μg / mL; Figure d shows the STYO of Staphylococcus aureus ATCC6538 under different treatments 9 / PI double-staining fluorescence images, where green represents live bacterial cells and red represents dead bacterial cells; Figure e is the scanning electron microscopy analysis results of Staphylococcus aureus ATCC6538 strain under different treatments, where the arrows represent the ruptured film and the green area represents the substance attached to the Staphylococcus aureus cells; Figure f is the crystal violet staining results of Staphylococcus aureus ATCC6538 strain under different treatments; Figure g is the laser confocal scanning result of the scratch area of L929 cells under different treatments, where the yellow line represents the boundary of the linear scratch; Figure h is the measurement result of O2 content in L929 cells under different treatments, where the red area represents the O2 probe Ru(dpp)3Cl2;
[0042] Fig.12 In the figure, Figure a and Figure b are the healing results and schematic diagrams of circular wounds in mice with various infectious wound models infected with Staphylococcus aureus ATCC6538 strains under different treatments at different times; Figures c, d, e and f are the histological analysis results of various wound samples after different staining, immunofluorescence treatment and immunohistochemistry treatment, among which the blue line in H&E indicates epidermal thickness, the green arrow in Masson indicates collagen deposition, the brown-yellow area in TGF-β1 indicates positive area, the red arrow in HSP70 indicates positive area, the green arrow in Gram indicates positive bacterial infection, the blue area and red area in CD31 indicate DAPI and vascular endothelial cells, respectively, the blue area and red area in TNF-α indicate DAPI and TNF-α, respectively, the green area in IL-6 indicates IL-6, and the red arrow in HIF-1 indicates HIF-1 positive area; Figure g is the relative fluorescence intensity of TNF-α in each wound sample; Figure h is the relative fluorescence intensity of IL-6 in each wound sample. DETAILED DESCRIPTION
[0043] The present invention provides a method for preparing a composite self-gelling powder, comprising the following steps:
[0044] (1) mixing 1,3,5-tri(4-aminophenyl)benzene (TAPB), 2,5-dimethoxyterephthalaldehyde (DMTP), acetonitrile, acetic acid and iron phthalocyanine and reacting for 5 to 36 hours, preferably 25 hours, to obtain a reaction solution;
[0045] (2) centrifuging the reaction solution, collecting the precipitate and drying it to obtain COF-Fe;
[0046] (3) calcining COF-Fe in an inert gas for 0.5 to 4 h, preferably 2 h, to obtain CCOF-Fe;
[0047] (4) CCOF-Fe, polyacrylic acid (PAA), polyacrylamide (PAM) and water are mixed, freeze-dried and ground for 5 to 20 min, preferably 10 min, to obtain a composite self-gel powder CCF@PP.
[0048] In the present invention, the mass ratio of TAPB and DMTP mixed in step (1) is 6-15:5-10, preferably 8-12:7-9, and more preferably 10:8;
[0049] The mass ratio of TAPB to iron phthalocyanine is 6-15:1.2-3, preferably 8-12:2-2.5, and more preferably 10:2.4;
[0050] The mass volume ratio of the TAPB and acetonitrile mixture is 6-15 mg:15-25 mL, preferably 8-12 mg:20 mL, and more preferably 10 mg:20 mL;
[0051] The mass volume ratio of the TAPB and acetic acid mixture is 6-15 mg: 0.2-0.7 mL, preferably 8-12 mg: 0.5 mL, and more preferably 10 mg: 0.5 mL;
[0052] The reaction temperature in step (1) is 20-30°C, preferably 25°C.
[0053] In the present invention, the preparation steps of the reaction solution in step (1) are: firstly, DMTP, acetonitrile and iron phthalocyanine are mixed and reacted for 1 hour, and then TAPB and acetic acid are added and mixed and reacted for 24 hours.
[0054] In the present invention, the centrifugal speed in step (2) is 800-1500 rpm, preferably 1000 rpm; the centrifugal time is 5-15 min, preferably 10 min;
[0055] The drying in step (2) is vacuum freeze drying, the vacuum freeze drying temperature is -60 to -20°C, preferably -40°C; the vacuum freeze drying time is 6 to 24 hours, preferably 12 hours;
[0056] The particle size of the COF-Fe in step (2) is 250-500 nm, preferably 350 nm.
[0057] In the present invention, the inert gas in step (3) is nitrogen or argon, preferably nitrogen;
[0058] The calcination temperature in step (3) is 500-1000° C., preferably 950° C.; the calcination heating rate is 2-10° C. / min, preferably 8° C. / min;
[0059] The particle size of the CCOF-Fe in step (3) is 200-450 nm, preferably 300 nm.
[0060] In the present invention, the mass ratio of the CCOF-Fe, PAA, PAM and water mixed in step (4) is 0.001-0.016:0.1-0.4:0.2-0.5:5-15, preferably 0.008:0.15:0.35:10.
[0061] In the present invention, the molecular weight of the PAA in step (4) is 120,000 to 300,000 Da, preferably 250,000 Da; the mass concentration of PAA is 5% to 15%, preferably 10%; purchased from Bailingwei Technology Co., Ltd.;
[0062] The PAM is non-ionic PAM, the molecular weight of the non-ionic PAM is 5000000-15000000Da, preferably 10000000Da; the mass concentration of the non-ionic PAM is 2%-10%, preferably 5%; it is purchased from Quanyong Co., Ltd.
[0063] In the present invention, the freeze-drying temperature in step (4) is -60 to -20°C, preferably -40°C; the freeze-drying time is 6 to 24 hours, preferably 12 hours.
[0064] The invention also provides composite self-gel powder prepared by the preparation method.
[0065] The invention also provides application of the composite self-gel powder in preparing antibacterial drugs.
[0066] The present invention also provides application of the composite self-gelling powder in preparing medicine for relieving and / or treating infectious wounds.
[0067] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0068] Among the reagents of the present invention, PAA was purchased from J&K Technology Co., Ltd., non-ionic PAM was purchased from Quanyong Co., Ltd., STYO 9 stain and PI stain were purchased from Thermo Fisher Scientific, USA, HAc-NaHAc buffer (pH=7.4) was from Fudan University, superoxide dismutase (SOD) detection kit-WST was purchased from Dojindo Chemical Research Institute, Japan, and calcein AM live cell labeling kit was purchased from Abcam, UK;
[0069] In the test materials of the present invention, the Staphylococcus aureus ATCC6538 strain was purchased from the American Type Culture Collection; the mouse fibroblast L929 cell line was purchased from Shanghai Mingjin Biotechnology Co., Ltd.; 8-week-old male Blab / C mice weighing 20-22 g were purchased from Shanghai Lingchang Biotechnology Co., Ltd.;
[0070] Among the instruments of the present invention, the Scientz-12 freeze dryer was purchased from Ningbo Xinzhi Biotechnology Co., Ltd., the 1400T tube furnace was purchased from Shanghai Quanshuo Electric Furnace Co., Ltd., the JPBJ-609L dissolved oxygen meter was purchased from Shanghai Precision Scientific Instrument Co., Ltd., the MDJ-D02H1 grinder was purchased from Bear Electric Co., Ltd., the Instron 3400 universal tensile testing machine was purchased from Instron Corporation of the United States, the CKX53 inverted fluorescence microscope was purchased from Olympus Corporation of Japan, the Regulus 8230 scanning electron microscope was used from the Advanced Low-Dimensional Materials Center of Donghua University, and the Spin SR10 laser confocal scanning microscope and the VS200 slide scanner were used from the School of Pharmacy of Fudan University.
[0071] Example 1: CCOF-Fe x Preparation
[0072] 0.8 g, 1.6 g, 2.4 g, and 3.2 g of iron phthalocyanine were mixed with 8 g of DMTP and 20 mL of acetonitrile, respectively, and ethanol was used as a control. After stirring and reacting at 25°C for 1 hour, 10 g of TAPB and 0.5 mL of acetic acid were added, and the reaction was stirred at 25°C for 24 hours, and the reaction liquid was collected; each reaction liquid was centrifuged at 1000 rpm for 10 minutes, the precipitate was collected and washed with anhydrous ethanol for 3 times, and then freeze-dried in a Scientz-12 freeze dryer at -40°C in a vacuum environment for 12 hours to obtain COF-Fe0, COF-Fe1, COF-Fe2, COF-Fe3, and COF-Fe4, respectively. The preparation process is as follows: Figure 1 As shown;
[0073] Each COF-Fe with a particle size of 350 nm was taken xThey were transferred to ceramic crucibles respectively, placed in a 1400T tube furnace for calcination in a nitrogen atmosphere, the heating rate was set to 8 ° C / min, and the temperature was raised to 950 ° C and then calcined for 2 h. After natural cooling, CCOF-Fe0, CCOF-Fe1, CCOF-Fe2, CCOF-Fe3, and CCOF-Fe4 were obtained respectively. The preparation process is as follows Figure 1 As shown;
[0074] The COF-Fe x and CCOF-Fe x The structure of each CCOF-Fe x The particle size, such as Figure 2 shown.
[0075] The results show that each COF-Fe x and CCOF-Fe x The morphology of COF-Fe x and CCOF-Fe x The morphology of CCOF-Fe x The particle size gradually increases; when CCOF-Fe4 is damaged, the particle size also decreases.
[0076] Example 2: Effect of the content of iron phthalocyanine on the x Impact
[0077] 200 μL of each CCOF-Fe prepared in Example 1 was added x and 1700 μL HAc-NaHAc buffer (pH = 7.4) and 100 μL H2O2 to obtain the CAT enzyme reaction system, and the CCOF-Fe x The CAT enzyme reaction system was used as the control (Contral), and then placed in a constant temperature water bath at 25°C for reaction. The oxygen production rate and oxygen production in each CAT enzyme reaction system were measured every 10 seconds using a JPBJ-609L dissolved oxygen meter; the superoxide dismutase (SOD) detection kit-WST was used to determine the oxygen production of each CCOF-Fe prepared in Example 1. x The SOD activity inhibition rate, such as Figures 3 to 5 shown.
[0078] The results showed that with the increase of phthalocyanine iron content, the oxygen production rate and oxygen production in each CAT enzyme reaction system gradually increased, among which the oxygen production rate and oxygen production in the CAT enzyme reaction system with CCOF-Fe3 were the largest; with the extension of reaction time, the oxygen production rate in each CAT enzyme reaction system decreased; CCOF-Fe3 also had the highest SOD activity inhibition rate. This shows that CCOF-Fe3 has the strongest scavenging ability for H2O2 and superoxide free radicals, so COF-Fe3 is called COF-Fe, and CCOF-Fe3 is called CCOF-Fe;
[0079] Comparing the morphology and structure of COF-Fe before calcination and CCOF-Fe after calcination, it was found that the Fe element was uniformly dispersed in CCOF-Fe, indicating that CCOF-Fe was successfully synthesized and the structure was stable, and it had the structural characteristics of micropores and mesopores.
[0080] The CAT activity of COF-Fe and CCOF-Fe was tested, and it was found that compared with COF-Fe, CCOF-Fe produced more oxygen under the same conditions, indicating that calcination can increase the active sites and make the catalytic activity of CAT enzyme higher, but the CAT activity will be significantly affected by the environmental pH. The CAT activity of CCOF-Fe is low under acidic conditions and high under neutral conditions.
[0081] Example 3: Mass ratio of polyacrylic acid and polyacrylamide for self-gelling powder PP x Impact
[0082] A 5% polyacrylamide solution with a molecular weight of 10000000Da and a 10% polyacrylic acid solution with a molecular weight of 250000Da were mixed uniformly according to the mass ratio of PAM to PAA of 1:9, 3:7, 5:5, 7:3, and 9:1, respectively, to obtain polymers. Each polymer was frozen in liquid nitrogen for 10 minutes, and then freeze-dried at -40°C for 12 hours using a Scientz-12 freeze dryer to obtain a freeze-dried sample; each freeze-dried sample was ground for 10 minutes using an MDJ-D02H1 grinder to obtain self-gel powder PP, 1:9 PP 3:7 PP 5:5 PP 7:3 PP 9:1 ,like Figure 6 As shown;
[0083] Take each gel powder PP x 0.5 g was mixed with 500 μL of deionized water to obtain PP x Gel, each PP xThe gel was placed between two steel plates and placed under a pressure of 1 kg for 5 min. The PP x The breaking force of the gel, such as Figure 7 shown.
[0084] The results showed that self-gelling powder PP 1:9 PP 3:7 Unable to form PP x Gel; PP prepared according to the mass ratio of PAM to PAA of 1:9, 3:7, 5:5, and 7:3 x The breaking strength of the gel increases in sequence, among which PP 7:3 The breaking strength of the gel is the largest and the adhesion is the strongest; when the amount of PAM added continues to increase, PP x The breaking strength of the gel is then weakened. This indicates that in the preparation of self-gel powder PP x In the process, the optimum mass ratio of PAM and PAA is 7:3; therefore, the self-gelling powder PP 7:3 It is called self-gel powder PP. 7:3 The gel is called PP gel.
[0085] Example 4: Composite self-gel powder CCF@PP x Preparation
[0086] 0.35 g of PAM and 10 g of water were mixed to obtain a PAM solution, to which 4 mg, 8 mg, 12 mg, and 16 mg of CCOF-Fe with a particle size of 300 nm prepared in Example 2 were added, respectively, with no CCOF-Fe added as a control, and the mixture was stirred for 24 h to uniformly disperse the CCOF-Fe, and then 0.15 g of PAA was added and stirred to obtain a mixed solution; each mixed solution was placed in liquid nitrogen and frozen for 10 min, and then freeze-dried at -40°C for 12 h using a Scientz-12 freeze dryer to obtain a freeze-dried sample; each freeze-dried sample was ground using an MDJ-D02H1 grinder for 10 min to obtain composite self-gel powders CCF@PP0, CCF@PP 0.4 、CCF@PP 0.8 、CCF@PP 1.2 、CCF@PP 1.6 ; Each composite self-gel powder CCF@PP x Mixed with deionized water to obtain CCF@PP x Gel, using the method described in Example 3 to determine the CCF@PP x The breaking force of the gel, such as Figures 8 to 10 shown.
[0087] The results show that CCOF-Fe can be evenly dispersed in the PAM solution and appears black. The higher the amount of CCOF-Fe added, the better the prepared composite self-gel powder CCF@PP. x The higher the hydrophobicity; composite self-gel powder CCF@PP 0.8 The water absorption rate of deionized water is the highest; the stress of CCF@PP0 gel without CCOF-Fe is the largest. With the increase of CCOF-Fe addition, CCF@PP x The stress of the gel gradually decreases, so the composite self-gel powder CCF@PP 0.8 It is called composite self-gel powder CCF@PP. 0.8 The gel is called CCF@PP gel;
[0088] The composite self-gelling powder CCF@PP can adhere firmly to pig skin and will not change with the twisting of the pig skin; on the more moist tissue surfaces such as pig heart and pig small intestine, the composite self-gelling powder CCF@PP can absorb excess liquid, quickly form CCF@PP gel, and firmly adhere to the tissue surface.
[0089] Example 5: Antibacterial effect of composite self-gel powder CCF@PP
[0090] Staphylococcus aureus ATCC6538 strain was cultured in LB medium until OD 600 =1.0, and then diluted to a concentration of 1×10 6 CFU / mL, and obtain the bacterial solution; the bacterial solution was added into the systems of groups A to L respectively and treated accordingly, wherein group A was added with 500μL bacterial solution alone, group B was 500μL bacterial solution + 500μL CCOF-Fe, group C was 500μL bacterial solution + 490μL CCOF-Fe + 10μL 1mmol / L H2O2, group D was 500μL bacterial solution + 500μL CCOF-Fe + near infrared (NIR), group E was 500μL bacterial solution + NIR, group F was 500μL bacterial solution + 10μL 1mmol / L H2O2 + NIR + 490μL PBS, group G was 500μL bacterial solution + 500μL PP gel, group H was 500μL bacterial solution + 490μL PP gel + 10μL 1mmol / L H2O2, group I was 500μL bacterial solution + 500μL CCF@PP gel, group J was 500μL bacterial solution + 500μL CCF@PP gel + NIR, group K was 500μL bacterial solution + 500μL CCF@PP gel + 10μL 1mmol / L H2O2, and group L was 500μL bacterial solution + 490μL CCF@PP gel + 10μL 1mmol / L H2O2 + NIR; NIR was irradiated with 808nm near-infrared for 5min, with an irradiation dose of 1.0W / cm2 After incubating each system at 37°C for 1 h, spread the plate on an agar plate and continue to culture at 37°C for 24 h. Count the colony forming units. Fig.11 As shown;
[0091] Referring to the operating instructions of STYO 9 stain and PI stain, the bacterial solution was treated with PBS, 1mmol / L H2O2, 125μg / mL CCF@PP gel + 1mmol / L H2O2 + NIR, 250μg / mL CCF@PP gel + 1mmol / L H2O2 + NIR, and 500μg / mL CCF@PP gel + 1mmol / L H2O2 + NIR, respectively. NIR was irradiated with 808nm near-infrared for 5min at an irradiation dose of 1.0W / cm 2 ; Then, the cells were stained with STYO 9 / PI double staining for 15 min in a dark environment, and the fluorescent images of live and dead bacterial cells were captured using a CKX53 inverted fluorescence microscope, as shown in Figure 2. Fig.11 As shown;
[0092] The bacterial solution was added into the systems of groups a to l respectively and treated accordingly, where group a consisted of 500 μL bacterial solution + 500 μL PBS, group b consisted of 500 μL bacterial solution + 500 μL CCOF-Fe, group c consisted of 500 μL bacterial solution + 490 μL 250 μg / mL CCOF-Fe + 10 μL 1 mmol / L H2O2, group d consisted of 500 μL bacterial solution + 500 μL 250 μg / mL CCOF-Fe + NIR, group e consisted of 500 μL bacterial solution + NIR, group f consisted of 500 μL bacterial solution + 10 μL 1 mmol / L H2O2 + NIR + 490 μL PBS, group g consisted of 500 μL bacterial solution + 500 μL 250 μg / mL PP gel, and group h consisted of 500 μL bacterial solution + 490 μL 250 μg / mL PP gel + 10 μL 1 mmol / L H2O2, group i was 500μL bacterial solution + 500μL 250μg / mL CCF@PP gel, group j was 500μL bacterial solution + 500μL 250μg / mL CCF@PP gel + NIR, group k was 500μL bacterial solution + 500μL 250μg / mL CCF@PP gel + 10μL 1mmol / L H2O2, group l was 500μL bacterial solution + 490μL 250μg / mL CCF@PP gel + 10μL 1mmol / L H2O2 + NIR; NIR was irradiated with 808nm near-infrared for 5min, with an irradiation dose of 1.0W / cm 2Each system was incubated at 37°C and 150 rpm for 4 h, then centrifuged at 5000 rpm for 10 min to collect bacterial cells, mixed with 2.5% glutaraldehyde, and stored at 4°C overnight to obtain a suspension; the suspension was washed three times with PBS, and then dehydrated with 30%, 50%, 70%, 90% and 100% ethanol solutions in sequence, with each stage lasting 15 min; the bacterial cells were analyzed using a Regulus 8230 scanning electron microscope, as shown in Figure 2. Fig.11 As shown;
[0093] A single colony of Staphylococcus aureus ATCC6538 was cultured in LB medium until OD 600 =1.0 to obtain a bacterial solution, 10 μL of the bacterial solution and 90 μL of LB medium were mixed thoroughly in a 96-well plate, and a biofilm was observed at the bottom of the culture well after incubation at 37°C for 72 h. Fresh LB medium was introduced every 24 h during this period. Each culture well was divided into 1 to 5 groups and treated accordingly, wherein group 1 was added with PBS, group 2 was added with 250 μg / mL CCF@PP gel, group 3 was 250 μg / mL CCF@PP gel + NIR, group 4 was 250 μg / mL CCF@PP gel + 1 mmol / L H2O2, and group 5 was 250 μg / mL CCF@PP gel + 1 mmol / L H2O2 + NIR; wherein NIR was irradiated with 808 nm near-infrared radiation for 5 min, with an irradiation dose of 1.0 W / cm 2 . Then, the residual biofilm was rinsed with PBS, and the crystal violet staining method disclosed by Huang Jiacheng et al. in the literature (Huang Jiacheng, Shao Xinxin, Li Haomiao, et al. Construction of an animal model of perfusion and flushing of early-stage bacterial biofilm formation after internal fixation surgery [J]. Chinese Journal of Tissue Engineering Research, 2024, 28(23): 3704-3708) was used to stain and quantify each biofilm, and the OD of each biofilm was measured. 590nm Values, such as Fig.11 As shown;
[0094] L929 cells were seeded into a 24-well plate, and a 200 μL pipette tip was used to make linear scratches on the L929 cells. Then, the dispersed L929 cell fragments were rinsed with PBS and the scratches were recorded. Each culture well was divided into groups (1) to (6) and treated accordingly, wherein 10 μL PBS was added to group (1), 10 μL 1 mmol / L H2O2 was added to group (2), 10 μL 70 μg / mL CCF@PP gel was added to group (3), 10 μL 700 μg / mL CCF@PP gel was added to group (4), 10 μL 700 μg / mL CCF@PP gel was added to group (5), 10 μL 70 μg / mL CCF@PP gel + 10 μL 100 μmol / L H2O2 was added to group (6), and 10 μL 700 μg / mL CCF@PP gel + 10 μL 100 μmol / L H2O2; each culture well was placed in an incubator for culture, and then stained with a calcein AM live cell labeling kit, and a SpinSR10 laser confocal scanning microscope was used to monitor and record cell migration at different time intervals, and three scratch areas were selected from each culture well and analyzed using Image J software, such as Fig.11 As shown;
[0095] L929 cells were seeded into 96-well plates and incubated under 5% O2 for 12 h, then 50 μmol / L O2 probe Ru(dpp)3Cl2 was added, and the cells were incubated under 5% O2 for 4 h. PBS, 100 μmol / L H2O2, 70 μg / mL CCF@PP gel, 700 μg / mL CCF@PP gel, 70 μg / mL CCF@PP gel + 100 μmol / L H2O2, and 700 μg / mL CCF@PP gel + 100 μmol / L H2O2 were added to each culture well, respectively, and the cells were cultured under 5% O2 and 100 μmol / L H2O2 for 6 h. After the culture was completed, the cells were rinsed with PBS three times to remove residual Ru(dpp)3Cl2, and the cells were observed under a SpinSR10 laser confocal scanning microscope at A 450nm Observe L929 cells under excitation light, such as Fig.11 shown.
[0096] The results showed that as the concentration of CCF@PP gel gradually increased, its inhibitory effect on Staphylococcus aureus ATCC6538 strain gradually increased; STYO 9 / PI double staining and morphological characterization of Staphylococcus aureus ATCC6538 strain indicated that the composite self-gelling powder CCF@PP had good antibacterial properties, and the detection results of L929 cells showed that the composite self-gelling powder CCF@PP could promote the growth of fibroblasts.
[0097] Example 6: Treatment of infected wounds with composite self-gelling powder CCF@PP
[0098] After the back hair of male Blab / C mice was shaved and disinfected with alcohol cotton, a circular wound with a diameter of 8 mm was made on the back of the mouse using a medical punch, and the circular wound was infected with Staphylococcus aureus ATCC6538 strain for 24 hours to establish an infected wound model mouse. The circular wound of each model mouse was treated with PBS, PP gel prepared in Example 3, CCOF-Fe prepared in Example 2, CCF@PP gel prepared in Example 4, CCOF-Fe+NIR, and CCF@PP gel+NIR, respectively, where NIR was irradiated with 808 nm near-infrared for 5 minutes, with an irradiation dose of 1.0 W / cm 2 ; Then the wounds were measured and recorded on the 0th, 3rd, 6th, 9th and 12th day of each treatment. On the 12th day of each treatment, wound tissues were collected from each infected wound model mouse and preserved in 4% paraformaldehyde solution to obtain wound samples; each wound sample was paraffin-embedded and sectioned, and each wound sample was subjected to hematoxylin-eosin staining (H&E), Masson trichrome staining (Masson), rapid Gram staining (Gram), CD31 immunofluorescence treatment (CD31), TNF-α immunofluorescence treatment (TNF-α), IL-6 immunofluorescence treatment (IL-6), transforming growth factor β1 immunohistochemical treatment (TGF-β1), heat shock protein 70 immunohistochemical treatment (HSP70), and hypoxia-inducible factor-1 immunohistochemical treatment (HIF-1) to obtain the corresponding slides, and each slide was scanned and histologically analyzed using a VS200 slide scanner, and the fluorescence area of TNF-α and IL-6 was quantitatively analyzed using Image J software, as shown in Fig.12 shown.
[0099] The results showed that the composite self-gel powder CCF@PP can promote the healing of infected wounds on mouse skin and reduce the inflammatory response of the wound.
[0100] It can be seen from the above embodiments that the present invention provides a composite self-gelling powder and a preparation method and application thereof. The composite self-gelling powder CCF@PP prepared by the present invention has strong adhesion, stability and good antibacterial properties, which can not only promote the healing of infected wounds and the growth of fibroblasts, but also reduce the inflammatory response of wounds.
[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a composite self-gelling powder, characterized in that: The steps include: (1) mixing 1,3,5-tri(4-aminophenyl)benzene, 2,5-dimethoxyterephthalaldehyde, acetonitrile, acetic acid and iron phthalocyanine and reacting for 5 to 36 hours to obtain a reaction solution; (2) centrifuging the reaction solution, collecting the precipitate and drying it to obtain COF-Fe; (3) calcining COF-Fe in an inert gas for 0.5 to 4 h to obtain CCOF-Fe; (4) CCOF-Fe, polyacrylic acid, polyacrylamide and water are mixed, freeze-dried and ground for 5 to 20 minutes to obtain a composite self-gel powder.
2. The preparation method according to claim 1, characterized in that: The mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde mixed in step (1) is 6-15:5-10; The mass ratio of the 1,3,5-tris(4-aminophenyl)benzene and iron phthalocyanine is 6-15:1.2-3; The mass volume ratio of the mixture of 1,3,5-tri(4-aminophenyl)benzene and acetonitrile is 6-15 mg:15-25 mL; The mass volume ratio of the mixture of 1,3,5-tris(4-aminophenyl)benzene and acetic acid is 6-15 mg:0.2-0.7 mL; The reaction temperature in step (1) is 20-30°C.
3. The preparation method according to claim 2, characterized in that: The centrifugal speed in step (2) is 800-1500 rpm, and the centrifugal time is 5-15 min; The drying in step (2) is vacuum freeze drying, the vacuum freeze drying temperature is -60 to -20°C, and the vacuum freeze drying time is 6 to 24 hours; The particle size of the COF-Fe in step (2) is 250 to 500 nm.
4. The preparation method according to claim 3, characterized in that: The inert gas in step (3) is nitrogen or argon; The calcination temperature in step (3) is 500-1000° C. The particle size of the CCOF-Fe in step (3) is 200 to 450 nm.
5. The preparation method according to claim 4, characterized in that: In step (4), the mass ratio of the CCOF-Fe, polyacrylic acid, polyacrylamide and water is 0.001-0.016:0.1-0.4:0.2-0.5:5-15.
6. The preparation method according to claim 5, characterized in that: The molecular weight of the polyacrylic acid in step (4) is 120,000 to 300,000 Da, and the molecular weight of the polyacrylamide is 5,000,000 to 15,000,000 Da.
7. The preparation method according to claim 6, characterized in that: The freeze-drying temperature of step (4) is -60 to -20°C, and the freeze-drying time is 6 to 24 hours.
8. The composite self-gel powder prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the composite self-gel powder according to claim 8 in the preparation of antibacterial drugs.
10. Use of the composite self-gel powder according to claim 8 in the preparation of a medicament for alleviating and / or treating infected wounds.
Citation Information
Patent Citations
Method for modifying catalytic performance of COFs (covalent organic frameworks) based electrocatalyst on basis of graphene loading
CN108671962A
Trichloroacetic acid electrochemical sensor with iron phthalocyanine modified metal-organic frameworks and preparation method thereof
CN110487862A
Carbon nanotube material derived from covalent organic framework and preparation method of carbon nanotube material
CN111977638A
Method for promoting dispersion of metal coordination covalent organic framework material in liquid phase
CN113185726A
Two-dimensional covalent organic framework material for electrocatalytic oxygen reduction and preparation method of two-dimensional covalent organic framework material
CN115160579A